2019
DOI: 10.1177/0022219419863790
|View full text |Cite
|
Sign up to set email alerts
|

New Teachers’ Perceptions on Being Prepared to Teach Students With Learning Disabilities: Insights From California

Abstract: Including students with learning disabilities (SWLDs) in general education classrooms is a priority nationwide. Consequently, now more than ever before in our nation’s history, university teacher education programs face increased responsibility to ensure general education teaching candidates receive adequate preparation to educate SWLDs. Many stakeholders believe that edTPA—a performance assessment used as a credential requirement—can be an important tool in helping to fulfill this goal. Utilizing survey data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…With a greater number of students, secondary teachers may have more opportunities to engage with those impacted by enforcement, and thus elements of their field placement are more directly tied to their perceptions of their abilities to support students. This aligns with prior research that has shown secondary teachers place a greater importance on the role of their supervisors with respect to preparedness to educate and support their students once inservice (Gottfried et al, 2019(Gottfried et al, , 2020.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…With a greater number of students, secondary teachers may have more opportunities to engage with those impacted by enforcement, and thus elements of their field placement are more directly tied to their perceptions of their abilities to support students. This aligns with prior research that has shown secondary teachers place a greater importance on the role of their supervisors with respect to preparedness to educate and support their students once inservice (Gottfried et al, 2019(Gottfried et al, , 2020.…”
Section: Discussionsupporting
confidence: 86%
“…Items soliciting perceptions of preservice training characteristics were reported on 5-point Likert-type scales, where preservice teachers could strongly disagree, disagree, neither agree or disagree, agree, or strongly agree to each question. These questions were derived from surveys used by Cohen and colleagues (2020) 2 surveying programs in a mid-Atlantic state and a pilot study at one of the TPPs in the UC System (Gottfried et al, 2019). As such, scales of preservice training used in these prior studies were constructed for the present study using confirmatory factor analysis (CFA) as described below.…”
Section: Datamentioning
confidence: 99%
“…Teachers often report feeling unprepared to work with students with disabilities [31,37,39,40]. Not all general education teacher preparation programs require an introductory course in basic special education constructs or working effectively with children with disabilities.…”
Section: General Education Teacher Preparation For Working With Students With Disabilitiesmentioning
confidence: 99%
“…They found that 19% of the programs for initial certification in elementary education did not require even an introductory course in the characteristics of disability, 67% did not offer a course in inclusion or differentiation, and 93% did not offer a course in collaboration between general education and special education teachers. Prospective general education teachers who are learning about working with students with disabilities must also have knowledge of the disability laws, policies, and practices of their school district and must be prepared through their teacher-training program to understand those laws, policies, and practices [39].…”
Section: General Education Teacher Preparation For Working With Students With Disabilitiesmentioning
confidence: 99%
“…Here /u/ represents a short sound. In the case of an open syllable, the vowel has a long sound like basin |ba| in an open syllable (Gottfried et al, 2019).…”
Section: Introductionmentioning
confidence: 99%